The IBNET Water Supply and Sanitation Blue Book 2014: The International Benchmarking Network for Water and Sanitation Utilities Databook - Danilenko, Alexander (World Bank, 2015)
Well-run water utilities play an important role in ending poverty and boosting shared prosperity. Consumers need reliable access to high quality and affordable water and sanitation services. To deliver these basic services efficiently and effectively requires high-performing utilities that are able to respond to urban growth, to connect with the poor, and to improve wastewater disposal practices.